ChemInform Abstract: Structure and Order in CoPt‐Type Nanoalloys: From Thin Films to Supported Clusters. Issue 47 (November 2015) - Andreazza, Pascal; Pierron‐Bohnes, Veronique; Tournus, Florent; Andreazza‐Vignolle, Caroline; Dupuis, Veronique
Abstract: Review: 442 refs.